2017
DOI: 10.1002/2016ja023789
|View full text |Cite
|
Sign up to set email alerts
|

Birkeland current boundary flows

Abstract: Intense zonal ion velocity jets in the northern nightside auroral zone are measured during quiet geomagnetic conditions by the Swarm satellites around 500 km altitude. These velocity jets, exceeding 1 km/s in over 50% of orbits measured, range from 20 to 100 km in meridional thickness and reach a maximum at the boundary between upward and downward field‐aligned current. On average they represent a potential difference of approximately 3 kV between the R1/R2 currents. This boundary also separates different regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 33 publications
8
40
1
Order By: Relevance
“…While there are some regions of upward FAC in individual events, we see no region of consistent upward FAC near SAID. The BCBF mark the boundary between upward R1 currents and downward R2 currents, as reported by Archer et al (2017). As one would expect based on their locations relative to the Birkeland currents, BCBF were on average poleward of SAID.…”
Section: Superposed Epoch Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…While there are some regions of upward FAC in individual events, we see no region of consistent upward FAC near SAID. The BCBF mark the boundary between upward R1 currents and downward R2 currents, as reported by Archer et al (2017). As one would expect based on their locations relative to the Birkeland currents, BCBF were on average poleward of SAID.…”
Section: Superposed Epoch Analysismentioning
confidence: 61%
“…The flow channels observed on the pass shown in Figure 1 (left column) between 68 ∘ and 70 ∘ MLAT meet the basic criteria of BCBF described in Archer et al (2017) but are also atypical in several ways. They looked at BCBF only while the AE index was <200 nT, and only one eastward and/or westward velocity spike was observed per auroral crossing.…”
Section: 1002/2017ja024577mentioning
confidence: 68%
“…Subsequent observations have shown that the edge of the diffuse aurora in omega bands corresponds to the boundary between the Region 1 and Region 2 current systems, mapping further downtail than the LLBL (Wild et al 2011). Strong shear flows have been observed by low-altitude spacecraft in this region during the occurrence of omega bands (Liu et al 2018), however these shear flows are a ubiquitous feature of the boundary between the R1 and R2 currents (Jiang et al 2015;Archer et al 2017) and as such, the occurrence of a shear flow does not appear to be sufficient to generate an omega band. This region is also generally stable to the KHI particularly when the coupling to the ionosphere is considered but may be unstable to the hybrid Kelvin-Helmholtz/Rayleigh Taylor Instability (Yamamoto 2009(Yamamoto , 2011.…”
Section: Drivers/causesmentioning
confidence: 98%
“…Ionospheric flows (or equivalently, electric field) associated with aurorae have been frequently observed since the early era of rocket and spacecraft missions (Burch et al, 1976;Marklund, 1984;Opgenoorth et al, 1990;Smiddy et al, 1980;Ziesolleck et al, 1983). A statistical study by Archer et al (2017) showed that the flows are most prominent at the boundary between Regions 1 and 2 (R1 and R2) currents. In the morning sector, an eastward flow peak is present near the R1/R2 current boundary during active times such as the substorm expansion and growth phases (Fujii et al, 1994;Jiang et al, 2015).…”
Section: 1002/2017gl076485mentioning
confidence: 99%